The Settlement of Management Rights Dispute or Utilization of Legal Certainty on the “Surat Ijo” Land Status - Karim; Jamil; Permanasari, Lolita; Wahyuningati, Edi; Ngaisah, Siti; Hartantien, Sinarianda Kurnia (Acta Universitatis Danubius. Juridica, 2023)
The land is one of the natural resources essential for human life. However, the land area is decreasing and limited because of the high population, natural conditions, and land area ownership. In Surabaya, land with Surat Ijo (green certificate) status has caused controversy between the government and Land Use Permits (IPT) holders. This study discusses the management and utilization of Surat Ijo land in Surabaya. This study uses normative legal methods with descriptive analysis. The data collection technique used in this study was a literature study. The results show that the concepts of land and management rights have been recognized by law in Indonesia. Surat Ijo or land use permits (IPT) holders only have management rights over the land they occupy but not the rights over the land. They can involve a third party to use the land, but the right still belongs to the Surabaya Government. Thus, it can be concluded that land with Surat Ijo status belongs to the Surabaya government, which residents with official IPT manage.